1997
DOI: 10.1177/174182679700400306
|View full text |Cite
|
Sign up to set email alerts
|

Fish Intake and Cardiovascular Risk Among Middle-Aged Japanese in Japan and Brazil

Abstract: Background Studies of immigrant populations are useful for analysis of the effects of environmental factors on cardiovascular disease. We have examined the association between dietary habit of fish intake and cardiovascular risk.Methods Population-based samples of 433 middle-aged Japanese men and women in Japan (Shimane (group JS) and Okinawa (group JO)) and 269 Japanese immigrants in Brazil ( S~O Paulo (group BS) and Campo Grande (group BC)), who had originally moved to Brazil mainly from Shimane and Okinawa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…One of the best correlations between CR and improvement in healthspan and prolonged life in humans is the long-lived population in Okinawa, Japan (Mizushima et al, 1997). In comparison to the rest of the Japanese population, Okinawan people usually combine an above-average amount of daily exercise with a below-average food intake (Willcox and Willcox, 2014).…”
Section: Behavioral Anti-aging Interventionsmentioning
confidence: 99%
“…One of the best correlations between CR and improvement in healthspan and prolonged life in humans is the long-lived population in Okinawa, Japan (Mizushima et al, 1997). In comparison to the rest of the Japanese population, Okinawan people usually combine an above-average amount of daily exercise with a below-average food intake (Willcox and Willcox, 2014).…”
Section: Behavioral Anti-aging Interventionsmentioning
confidence: 99%
“…Taurine plays an important role in several essential processes such as membrane stabilization, osmoregulation, anti-oxidation and development of the central nervous system and the retina (O'Flaherty et al, 1997;Schaffer et al, 2000). Suggestions have been put forward of reduced cardiovascular risk through the combined effects of taurine and n-3 PUFA (Mizushima et al, 1997;Yamori et al, 2001). The anti-oxidative properties of taurine could be of general value, at levels higher than those needed to prevent deficiencies.…”
Section: Introductionmentioning
confidence: 98%
“…Many large-scale studies, including primary and secondary prevention clinical trials and metaanalysis of cohorts, have concluded that consumption of fatty fish, fish oils or individual n-3 PUFA is an effective dietary strategy to lower CVD morbidity, mortality, as well as classic and emerging risk factors listed above [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In addition, n-3 PUFA have been shown to improve a number of cardiac hemodynamic factors such as blood pressure [35,36], left ventricular diastolic filling [37], heart rate [38,39] and endothelial function [40,41].…”
Section: Introductionmentioning
confidence: 99%